Developments in e-government : a critical analysis - Griffin, David, 1953-; Trevorrow, Philippa; Halpin, Edward F. (Innovation and the public sector ;, 2007)
Sets out to provide a critical evaluation of developments in e-government. This book examines the emerging area of e-democracy, in which technology is being utilized to provide a digital presence for the democratic processes of government. It is a synthesis of theoretical contributions and empirical investigations.